Fiscal Discipline and the Cost of Public Debt Service : Some Estimates for OECD Countries - Caselli, Francesco (IMF Working Papers; Working Paper, 1998)
Is there any systematic explanation of variations in the cost of debt servicing over time and across countries? This paper examines the influence of fiscal variables on borrowing costs in a panel of OECD countries, showing that these variables have a significant role. In particular, an improvement of the primary fiscal balance is associated with a significant reduction in debt-servicing costs, amplifying the effects of primary adjustment on the fiscal position. A significant country-specific component remains, however; several explanations for this component are discussed, including debt management and market infrastructure.